Combined arteriovenous sheathotomy and intraoperative intravitreal triamcinolone acetonide for branch retinal vein occlusion. Issue 11 (9th September 2010) - Hwang, John C; Gelman, Susan K; Fine, Howard F; Chang, Stanley; Del Priore, Lucian V
Abstract : Purpose: To describe the treatment of macular oedema secondary to branch retinal vein occlusion (BRVO) with concomitant pars plana vitrectomy/arteriovenous sheathotomy and intraoperative intravitreal triamcinolone acetonide. Methods: Retrospective case series. Results: Four eyes of four patients were identified. Patients improved from a mean best-corrected visual acuity of 20/124 at baseline to 20/122 at month 1, 20/83 at month 3, 20/74 at month 6, 20/59 at month 9 and 20/44 at month 12 (p=0.01). All patients demonstrated improvement in visual acuity and macular oedema on fluorescein angiography and/or optical coherence tomography (OCT). Conclusion: For patients with persistent macular oedema due to BRVO refractory to pharmacotherapy and/or laser photocoagulation, concomitant pars plana vitrectomy with arteriovenous sheathotomy and intravitreal triamcinolone may improve best-corrected acuity and reduce macular oedema on fluorescein angiography and OCT.